Modelling futility in the setting of fertility treatment. Issue 5 (17th March 2022) - Polyakov, Alex; Gyngel, Christopher; Savulescu, Julian
Abstract: When is a fertility treatment futile? This question has great practical importance, given the role futility plays in ethical, legal and clinical discussions. Here, we outline a novel method of determining futility for IVF treatments. Our approach is distinctive for considering the economic value attached to the intended aim of IVF treatments, i.e. the birth of a child, rather than just the effects on prospective parents and the health system in general. We draw on the commonly used metric, quality-adjusted life years (QALYs), to attach a monetary value to new lives created through IVF. We then define futility as treatments in which the chance of achieving a live birth is so low that IVF is no longer a cost-effective intervention given the economic value of new births. This model indicates that IVF treatments in which the chance of a live birth are <0.3% are futile. This suggests IVF becomes futile when women are aged between 47 and 49 years of age. This is notable older than ages currently considered as futile in an Australian context (∼45). In the UK, government subsidized treatment with the couple's own gametes stops at the age of 42, while privately funded treatments are self-regulated by individual providers. In most European countries and the USA, the 'age of futility' is likewise managed by clinical consensus.